The professionalization of engineering and the construction of modern Peru (1850-1930) - Lizarme Villcas, Nashely Yuvitza (2022)
The expansion of public works that began in the second half of the 19th century generated important economic, political, and cultural transformations in Peruvian society. It promoted the formation of a professional class made up of experts in planning, execution and administration of infrastructure projects and the exploitation of natural wealth. This article analyzes the professionalization of Engineering in Peru as part of a broader process that begins with the search for the State, with the collaboration of some sectors of civil society, to modernize the productive structures and form a capable ruling class. leading national modernization projects. In addition, the agency capacity of this professional sector to develop its own professionalization strategies aimed at legitimizing its discourse and its professional practice beyond the state sector is considered. Finally, it examines how both processes described above influenced the formation of a social concern in the engineering guild, which led to the generation of technical proposals for modernization of a nationalist and pro-industrial nature.